Peran Kode Etik dalam Meningkatkan Kualitas Pembelajaran Agama Kristen - Dorlan Naibaho; Tabita Mutia Tambunan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The code of ethics serves as a guideline for educators in carrying out their professional duties, especially in Christian Religious Education (PAK). This study aims to explore the role of the code of ethics in improving the quality of PAK learning. Using a qualitative approach, this study utilized literature studies, observations, and interviews with PAK teachers at the secondary school level. The findings indicate that consistent application of the code of ethics helps create a conducive learning environment, while deepening students' understanding of Christian values. By adhering to the code of ethics, teachers can act professionally, fairly, and with integrity, thereby increasing trust between teachers and students. In addition, the code of ethics is an important guide in overcoming learning challenges, such as the diversity of student backgrounds and curriculum changes. This study concludes that the code of ethics has an important role in improving the quality of PAK learning through strengthening teacher character and creating an inclusive learning atmosphere.